Pengaruh Jenis dan Penambahan Pengasam Alami terhadap Sifat Fisik dan Kimia Sirup Pepino - Senja Oktavia; Reni Astuti Widyowanti; Adi Ruswanto (Program Studi Teknologi Hasil Pertanian, 2024)
This study aimed to: (1) determine the effect of type and addition of natural acidifier on the characteristics of pepino syrup; (2) determine the composition of type and addition of natural acidifier that produces pepino syrup that is most preferred by panelist. This research used the Completed Blok Design (CBD) method with 2 factors. The first factor was the type of citrus (A) with 3 levels, namely (A1 = lime), (A2 = lemon), (A3 =squeezed citrus). The second factor was the addition of natural acidifier based on the volume base of 200 ml pepino juice with 3 levels, namely (B1=2,5%), (B2=5%), (B3=7,5%). The results showed that the type of orange and the addition of natural acidifier influenced all physical properties (viscosity, total color difference), chemical properties (total soluble solids, pH, vitamin C, and antioxidants), and organoleptic (color, aroma, taste) of pepino syrup. Sample A3B2 with the type of squeezed oranges and the addition of 5% natural acidifier was the most favored pepino syrup by panelists with a score of 6, category like.